Cushing’s syndrome: diagnostic labyrinths - A. R. Volkova; G. V. Semikova; M. E. Chernaya; E. N. Ostrouhova; A. V. Lisker; E. V. Volkova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
In the practice of a doctor of any specialty, patients with hypercorticism – a syndrome of excess glucocorticoids level in the body – are not uncommon. Despite the fact that most of these patients have characteristic appearance and clinical manifestations, the correct diagnosis is often established months or even years after the first complaints.The objective of this article was to demonstrate the clinical cases of patients with hypercorticism of various genesis, as well as a short theoretical reference based on the National Guidelines for the Management of Patients with Cushing’s Syndrome (2016).